The Effect of Pictorial versus Linguistic Context on Iranian EFL Learners’ Reading Comprehension - Mohammad Reza Khodadust; Sheida Ahmadi Navareh; Fatemeh Faramarzi Kohnehshahri (Iranian Journal of Educational Research, 2025)
Objective: The objective of this study was to comparatively examine the effects of pictorial versus linguistic context on Iranian EFL learners’ reading comprehension. Methods: The study involved 60 female EFL learners from the Abidar Private Language Institute during the spring term of 2022 in Sanandaj, Iran; they were selected based on their scores from the Nelson Proficiency Test. Participants were divided into two groups: an experimental group exposed to both pictorial and linguistic contexts, and a control group exposed solely to linguistic context. After administering a 25-item multiple-choice reading comprehension pretest, both groups were differently taught based on American English File (3rd edition). A parallel reading comprehension post-test was conducted to assess the outcomes after the treatment. Results: Data analysis indicated significant differences in reading comprehension scores between the two groups, demonstrating that the inclusion of pictorial context alongside linguistic context positively influenced learners' performance. Conclusions: The findings suggest that incorporating pictorial elements in reading materials can enhance EFL learners' reading comprehension. This has implications for educational policymakers, textbook designers, material developers, language teachers, and learners, advocating for the use of adequate visual contexts to facilitate more effective learning.